MINING AND PRODUCTIVE SPECIALIZATION: ECONOMIC IMPACTS OF THE COLLAPSE OF THE DAM OF FUNDÃO IN MARIANA/BRAZILzil (Gestão & Regionalidade, 2022)
This paper analyzes the economic impacts in the municipality of Mariana from the Fundão Dam rupture occurred at the end of 2015. The central hypothesis is that economic dependence on the mineral extraction sector makes this municipality more vulnerable to adverse shocks affecting this productive sector, compromising its job recovery capacity. In order to calculate the impacts of this disaster, datas on formal employment estimated through the Synthetic Control Method were used. The results showed that, although Mariana and its synthetic version show similar formal employment trajectory in the pre-shock period, Mariana recovered employability in the second year after the dam rupture, unlike the control group. However, this result is not due to the recovery of formal employment based on sustainable economic diversification strategies, but essentially by dependence of the mining activity and the post-disaster remediation actions that has been gradually implemented in order to recover affected areas.